Survey on The Level of Farmers Understanding Regarding Anthraxnose Disease on Cayaly Plants - Molebila, Didiana Yanuarita; Manek, Marisa Lilisanti; Duka, James A (JURNAL AGRIBISAINS, 2024)
Anthracnose is an important disease in cayenne pepper plants that can cause yield loss. The aim of this research is to determine the presence of anthracnose disease in cayenne peppers in Kopidil Village, and also the level of farmers’ understanding of the existence of this disease. The research was conducted in April-July 2023 in Kopidil Village with a sample size of 30 respondents. Data was collected using direct interview techniques with farmers with questionnaires. The data obtained was analyzed quantitatively descriptively using descriptive statistics such as percentages and averages. The research results show that 70% of farmers fall into the category of high to very high understanding, and 35.85% of farmers are very aware of the existence of anthracnose disease in cayenne pepper plants in Kopidil Village.